PELATIHAN DEMPLOT PENGOLAHAN LAHAN TANPA BAKAR GUNA MENINGKATKAN PRODUKTIVITAS KELADI DI DESA WAJOK HILIR - Henny Herawati; Kartini Kartini; Tatang Abdurrahman; Aji Ali Akbar (JUARA: Jurnal Wahana Abdimas Sejahtera, 2021)
Wajok Hilir Village is a peatland, agricultural have been going on for generations. The taro plant is one of the leading plants. However, in the last 10 years, productivity is only about 3-5 ounces per stem. This has resulted in the community no longer interested in cultivating taro plants. To increase the people's interest in planting taro, it is necessary to carry out training and practice by making a demonstration plot as a pilot. This activity aims to educate partners and residents in Wajok Hilir Village about how to farm taro so that productivity increases. The training provided was in the form of education on land management without burning. The method used in this activity is to provide training with the lecture and discussion method and direct practice in the taro demonstration plot. The partner of this activity is the Palaguna Farmer Group in Wajok Hilir Village. This training activity is a community service activity funded by the Higher Education DRPM 2020 through the Village Partners Development Program (PPDM) scheme. The result of this activity is that taro productivity can be increased and at the same time can increase the knowledge and skills of the Partners and residents of Wajok Hilir Village. This activity is also expected to increase the income of Partners in particular and the people of Wajok Hilir Village in general.